Pengembangan Sistem Informasi Simpan Pinjam (Studi Kasus : Koperasi Kencana Sejahtera Baiturrahmah) - Javiera Rahmadhany; Djoko Pramono; Welly Purnomo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Information systems can be applied in all types of organizations, including financial institutions such as cooperatives. Based on an interview with Mr. Marzuki S.H as the head of the Kencana Sejahtera Baiturrahmah Cooperative, it was found that several problems occurred in savings and loan activities. Among them are the process of recording and making savings and loan transaction reports that are still manual. This causes data to be not well organized, causing data to be lost and causing data recording errors and disrupting the reporting process. To solve this problem, an information system was developed using the SDLC Waterfall method. The needs analysis process resulted in 4 aktors and 14 functional requirements. Then the design is carried out using UML diagrams and implemented using object-oriented programming with the Codeigniter framework. The testing process is carried out by doing blackbox testing to get 100% valid results, then testing the Systen Usability Scale on 4 users getting an average of 76.25%, meaning that the system developed into the criteria of good.